2020
DOI: 10.1002/2050-7038.12541
|View full text |Cite
|
Sign up to set email alerts
|

Research on aerodynamic characteristics of wind turbine airfoil and blade in sand‐wind environment

Abstract: In Northwest China, wind resources are especially abundant, but this area is also seriously affected by sandy environments, so any wind turbines in this area are definitely affected by the sand-wind flow. Therefore, the shear stress transport k-ω turbulence model and discrete phase model are both used for the simulation of an S809 airfoil to study the influence of sandy environments on the aerodynamic performance. Based on this, the modified blade element momentum theory will be used to design wind turbines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The variation of airfoil performance under different leading-edge erosion depths and thicknesses is of great significance for the safety and maintenance of turbine blades. According to the depth of the leading-edge erosion morphological features, the erosion is divided into sand holes (0.51 mm), small pits (2.54 mm), and delamination (3.81 mm) [10]. In wind turbine blades (Vestas V47) that have been working in the desert for 12 years without maintenance [4], the severity of the erosion of the leading edge increases towards the blade tip.…”
Section: Erosion Typementioning
confidence: 99%
See 1 more Smart Citation
“…The variation of airfoil performance under different leading-edge erosion depths and thicknesses is of great significance for the safety and maintenance of turbine blades. According to the depth of the leading-edge erosion morphological features, the erosion is divided into sand holes (0.51 mm), small pits (2.54 mm), and delamination (3.81 mm) [10]. In wind turbine blades (Vestas V47) that have been working in the desert for 12 years without maintenance [4], the severity of the erosion of the leading edge increases towards the blade tip.…”
Section: Erosion Typementioning
confidence: 99%
“…They found that the maximum lift coefficient decreased by 35-61%, and the drag coefficient increased sharply by 131%-217%. Li et al [10] established a geometric model of leading-edge erosion by modifying the leading edge of the wind airfoil type. Their results indicated that leading edge erosion aggravates flow separation near the trailing edge.…”
Section: Introductionmentioning
confidence: 99%
“…Salem (Salem et al , 2013) developed a CFD model coupled with a sand particle deposition model to predict the airfoil profile for sand deposition and calculate the aerodynamic characteristics of the sand deposition airfoil profile. Wang (Wang et al , 2023) and Li (Li et al , 2021) conducted a study of the dynamic stall of the S809 airfoil in a sandy environment. Hasan (Hasan et al , 2022b; Hasan and P, 2022a) studied the influence of supercritical airfoil on helicopter characteristics and found that supercritical airfoil can increase efficiency and produce good aerodynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In a related study, Rezig et al [2] scrutinized the performance of blade surface materials following deterioration in a wind-sand environment. Meanwhile, Li et al [3] conceptualized and designed a wind turbine engineered to operate efficiently in both clean and sandy environments, incorporating advancements rooted in blade velocity momentum theory.…”
Section: Introductionmentioning
confidence: 99%